Nuclear Structure from a Simple Perspective (Oxford Studies in Nuclear Physics) - Casten, R. F. (Oxford University Press, 2011)
This book provides a useful survey and assessment of the study of low-energy collective and single particle excitations of medium and heavy nuclei. An ideal resource for graduate students, the book covers both experimental and theoretical perspectives. The author's simple intuitive approach will help the reader to understand the empirical systematics as well as detailed model calculations, without recourse to complex--and often--confusing formalism.